2013
DOI: 10.1111/ped.12064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early measles vaccination (AIKC strain) for preterm infants

Abstract: Early immunization at 6 months of age is effective to protect preterm infants in the outbreak setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…During the last outbreak of measles in the Netherlands, an additional dose of MMR vaccine was also offered [49]. Evidence for MMR vaccination at 6 months in preterm infants is scarce, but Ichikawa et al showed that early immunization at 6 months of age was protective against measles in 17 preterm infants [50]. If there is no direct risk of contact with the viruses, longer protection by maternal antibodies in combination with the first vaccination after 12 months (as previously recommended) may increase protection.…”
Section: Discussionmentioning
confidence: 99%
“…During the last outbreak of measles in the Netherlands, an additional dose of MMR vaccine was also offered [49]. Evidence for MMR vaccination at 6 months in preterm infants is scarce, but Ichikawa et al showed that early immunization at 6 months of age was protective against measles in 17 preterm infants [50]. If there is no direct risk of contact with the viruses, longer protection by maternal antibodies in combination with the first vaccination after 12 months (as previously recommended) may increase protection.…”
Section: Discussionmentioning
confidence: 99%
“…These two stains show some differences with regard to immunogenicity. 12,23,24 As a conclusion, our findings showed that in the study region, after the MMR vaccination, the seroconversion rates for measles are in the acceptable range, even though compared with other countries, there is still room for more improvement. Also, considering the fact that with herd immunities below 95% achieving measles elimination would in fact be out of reach, this achievement is a necessity.…”
Section: Discussionmentioning
confidence: 51%
“…In similar studies, the time interval between the vaccination and the post-vaccination blood sampling for the evaluation of immune response has usually been 4 to 6 weeks. [10][11][12] In the pre-elimination era, even in developed countries, the persistence of maternal antibodies even beyond 12 months of age had always been mentioned as one of the well-known mechanisms of measles vaccine failure. 13,14 As it was mentioned earlier, in the present study, 10 participants (3.7%) had protective levels of antibody before the vaccination, and they were not included in the calculations for seroconversion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Published evidence from observational studies shows that up to 8.9% of healthy children who received 2 doses of a MMR vaccine do not show seroprotective levels of anti-measles IgG at 7.4 years after the last immunization, and post-vaccination seroconversion does not occur in 2–10% of the subjects [ 37 43 ]. However, in our study, seroprotective levels of anti-measles antibodies were found in all preschool children immunized with MMR vaccine, both those born preterm and full-term.…”
Section: Discussionmentioning
confidence: 99%